Internalization of Local Traditions in Child Marriage from the Perspective of Maqasid Al-Usrah - Naimah, Farida Ulvi; Rokhman, Mauhibur; Hali, Ali Usman; Maarif, Muhammad Anas; Sirojuddin, Akhmad (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
Child marriage is still widely practiced in many regions of Indonesia, justified by theological reasons that it is entirely permissible. Marrying children at a young age is also seen by many as an achievement, as it is believed to help prevent them from engaging in promiscuous behavior. These issues have prompted research into child marriage from the perspective of maqāṣid al-usrah. The article aimed to describe the internalization of the Sundanese tradition into child marriage law from the maqāṣid al usrah perspective. This article used qualitative field research with sociology, anthropology, and usul-fiqh approaches. Data collection techniques were interviews, participant observation, and documentation. The informants were the head of KUA (Office of Religious Affairs), mudin (imams), religious leaders, and education practitioners. The study showed that the pattern of internalizing the Sundanese tradition into child marriage law is dominant, assisted by religious leaders as a catalyst to allow child marriage laws. There is a product of fiqh in the internalization of child marriage law, entitled the book Kitab an-Nikah. But, according to maqāṣid al-usrah, the child marriage law in Brebes is irrelevant.